A rapid removal of Phaeocystis globosa from seawater by peroxymonosulfate enhanced cellulose nanocrystals coagulation - Mingda Che; Cancan Shan; Renliang Huang; Mei Cui; Wei Qi; Jiří Jaromír Klemeš; Rongxin Su (Ecotoxicology and Environmental Safety, 2023)
Cellulose nanocrystals (CNC) are recognized as promising bio-based flocculants for controlling harmful algal blooms (HABs). Due to the charge shielding effect in seawater and the strong mobility of algae cells, CNC can’t effectively remove Phaeocystis globosa from seawater. To solve this problem, peroxymonosulfate (PMS) was used to enhance the coagulation of CNC for rapidly removal of P. globosa. The results showed that 91.7% of Chl-a, 95.2% of OD680, and 97.2% of turbidity of P. globosa were reduced within 3 h with the use of 200 mg L−1 of CNC and 20 mg L−1 of PMS. The removal of P. globosa was consisted of inactivation and flocculation. Notably, electron paramagnetic resonance (EPR) spectrums and quenching experiments revealed that the inactivation of P. globosa was dominated by PMS oxidation and 1O2. Subsequently, CNC entrained inactivated algal cells to settle to the bottom to achieve efficient removal of P. globosa. The content of total organic carbon (TOC) and chemical oxygen demand (COD) decreased significantly, indicating that a low emission risk of algal cell effluent was produced in the CNC-PMS system. In view of the excellent performance on P. globosa removal, we believe that the CNC-PMS system has great potential for HABs treatments.